Production and Cost Functions and their Application to the Port Sector : A Literature Survey - Tovar, Beatrice; Jara-Diaz, Sergio; Trujillo, Lourdes (World Bank, Washington, DC, 2014)
Seaports provide multiple services to ships, cargo, and passengers. These services can be performed by a combination of public and private initiatives. Usually, the role of public sector institutions is to regulate and supervise private firms. In performing that task public sector institutions require in-depth knowledge of firms' cost structure. This paper offers a review of the literature about ports' cost structure and of its implications for regulation. The paper argues that the operation of port terminals should be analyzed by means of multiproduct theory. This approach allows the calculation of several cost indicators (economies of scale, scope, and so forth) which are key tools to help regulators.